Moving to Opportunity (MTO) for Fair Housing Demonstration: Interim Impacts Evaluation, Tier 1 Restricted Access Data, 1994-2001 (United States) - Orr, Larry ([Verlag nicht ermittelbar], 2011)
Moving to Opportunity (MTO) was designed to answer questions about what happens when very poor families have the chance to move out of subsidized housing in the poorest neighborhoods of five very large American cities. MTO was a demonstration program: its approach combined tenant-based housing vouchers with location restrictions and housing counseling. MTO was also a randomized social experiment, carefully designed and rigorously implemented to test the effects of this approach on participating families. The interim evaluation included the collection of data on a wide range of outcomes that could potentially be affected by the MTO intervention. These outcomes fit into 6 study domains: (1) mobility, housing, and neighborhood, (2) adult and child physical and mental health, (3) child educational achievement, (4) youth delinquency and risky behavior, (5) adult and youth employment and earnings, and (6) household income and public assistance receipt. The restricted access data being made available through ICPSR includes many such analytic variables constructed from surveys and administrative data. The Tier 1 data also includes a census tract ID that allows researchers to link other neighborhood-level data.